2020
DOI: 10.1016/j.akcej.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Signless Laplacian spectrum of power graphs of finite cyclic groups

Abstract: In this paper, we have studied the Signless Laplacian spectrum of the power graph of finite cyclic groups. We have shown that n À 2 is an eigen value of Signless Laplacian of the power graph of Z n , n ! 2 with multiplicity at least /ðnÞ: In particular, using the theory of Equitable Partitions, we have completely determined the Signless Laplacian spectrum of power graph of Z n for n ¼ pq where p, q are distinct primes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In [9], it is shown that Laplacian spectral radius of power graph of any finite group coincides with the order of group G. Spectral properties of adjacency matrix of P(G) were investigated in [15]. Other spectral results of power graphs can be seen in [5,18,19,20,21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In [9], it is shown that Laplacian spectral radius of power graph of any finite group coincides with the order of group G. Spectral properties of adjacency matrix of P(G) were investigated in [15]. Other spectral results of power graphs can be seen in [5,18,19,20,21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The adjacency spectrum, the Laplacian, the normalized Laplacian and the signless Laplacian spectrum of power graphs of finite cyclic and dihedral groups have been investigated in [13,16,28,29,43,35,44].…”
Section: Normalized Distance Laplacian Eigenvalues Of Power Graphs Of...mentioning
confidence: 99%
“…Let G be a finite group of order n with identity element e. Chakrabarty et al [7] defined the undirected power graph P(G) of a group G as an undirected graph with vertex set as G and two vertices x, y ∈ G are adjacent if and only if one is the positive power of other, that is, x i = y or y j = x, for positive integers i, j with 2 ≤ i, j ≤ n. For some recent work on power graphs, we refer to [1,5,7,8,15] and the references therein. The adjacency spectrum, the Laplacian and the signless Laplacian spectrum of power graphs of finite cyclic and dihedral groups has been investigated in [3,6,11,16,20]. (n i + 1), so the order of the graph…”
Section: A α -Spectrum Of Power Graphs Of Certain Finite Groupsmentioning
confidence: 99%